Effects of foliar biofertilization on the Water Use Efficiency in different varieties of basil (Ocimum basilicum L.) - Huito-Tarquino, Luis Eduardo (2022)
Introduction. Basil (Ocimum basilicum L.) is a little-known crop in the Bolivian highlands as its response to water use efficiency (WUE) in a Walipini-type greenhouses. Objective. To evaluate the behavior of two varieties of basil and the water use efficiency (WUE) in the application of foliar biofertilizer in a Walipini-type greenhouse. Materials and methods. The experiment was installed at the Ventilla Ecological Farm, in the Central Highlands of Bolivia, with an experimental period of 135 days (July 13 to November 25), 2014. A factorial experiment with two factors (varieties: Nufar F1 and Italian Large Leaf) and two levels of foliar biofertilizer (Biol) was used under a completely randomized block design. Results. Through the WUE, specific leaf area, and net assimilation rate relationship, it was observed that basil had a better development in Walipini-type greenhouse (underground greenhouse) since biomass accumulation was not significantly affected. The results showed that the production of basil in this environment using foliar biofertilizer, Biol, differ mainly by the variety rather than by the doses of Biol, showing that Nufar F1 had better development. Conclusion. A significant relationship was observed between Nufar F1 and Italian large Leaf for biomass weight when applying Biol at two different levels. It shows that there does not necessarily have to be a positive and significant relationship between biomass accumulation and WUE, so it is presumed that basil can develops regularly in Walipini-type greenhouses under semi-arid region conditions.